Otimização do processamento de partículas lead-free para aplicação em compósitos polímero/cerâmica com propriedades piezoelétrica e fotoluminescente - Teixeira, Guilhermina Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The main goal of this research was improved the process for obtaining of NaNbO3 lead-free particles, in order to use the particles in flexible composites with piezoelectric and photoluminescence properties. By microwave-assisted hydrothermal synthesis, Na2Nb2O6.H2O fiber-like particles (a metaestable phase resulting from crystallization of NaNbO3) and NaNbO3 cubic-like particles were obtained. By thermal treatment, the Na2Nb2O6.H2O fiber-like particles were converted to NaNbO3 fiber-like particles, maintaining the anisotropic morphology of the Na2Nb2O6.H2O. After the characterization, the NaNbO3 fiber-like particles and cubic-like particles wich presented the best characteristics were chosen to be combined with PVDF to make composites. Knowing of good properties of materials obtained from anisotropic particles, and their influence in composites characteristics, a conductor polymer was inclused in composite composition. For this, the NaNbO3 fiber like particles were partially covered by PAni polymer in the state conductive. Using different volume fraction of NaNbO3 particles immersed in PVDF polimeric matrix, the composites were obtained by hot press. The results showed that the increasing of vome fraction of NaNbO3 improve the electric properties of materials, but reduced the flexibility. The anisotropic of the particles influenced positively in the electric and optical properties of composites. The composites obtained from NaNbO3 fiber-like presented better propperties tha composites obtained from NaNbO3 cubic-like particles. The PAni presence in the composites improved the electric properties, but reduced the photoluminescence emission. The composites obtained from anisotropic NaNbO3 without PAni were the materials that showed simultaneously the best combination of piezoelectric and photoluminescence properties. These composites can be used in piezophotonic devices.

O principal objetivo deste trabalho foi a otimização do processo para a obtenção de partículas lead-free de NaNbO3, visando a aplicação das mesmas em compósitos flexíveis com propriedades piezoelétrica e fotoluminescência. Por meio da síntese hidrotérmica assistida por micro-ondas, foram obtidas partículas na forma de fibras de Na2Nb2O6.H2O (uma fase metaestável decorrente da cristalização do NaNbO3) e cubos de NaNbO3. Realizando tratamento térmico das fibras de Na2Nb2O6.H2O as mesmas foram convertidas a NaNbO3 mantendo a morfologia anisotrópica do Na2Nb2O6.H2O. Após realizadas as devidas caracterizações, foram escolhidas as partículas de NaNbO3, tanto na forma de fibras como na forma de cubos, com as melhores caracteristicas, a fim de serem incorporadas ao polímero PVDF para a formação dos compósitos. Sabendo-se das boas propriedades apresentadas por materiais obtidos à partir de partículas anisotrópicas, e da influência nas características dos compósitos devido a inclusão de um polímero condutor em sua composição, as fibras de NaNbO3 foram recobertas parcialmente com o polímero PAni na sua forma condutora. À partir de prenssagem a quente, utilizando diferentes frações volumétricas de NaNbO3 imersas na matriz polimérica de PVDF, foram obtidos compósitos com NaNbO3 na forma de cubos, NaNbO3 na forma de fibras e NaNbO3 na forma de fibras recobertas com PAni. Os resultados mostraram que o aumento da fração volumétrica de NaNbO3 aumenta a eficiência das propriedades elétricas dos materiais, porém diminui a flexibilidade. A anisotropia das partículas de NaNbO3 influenciou positivamente nas propriedades elétricas e ópticas dos compósitos, uma vez que os compósitos obtidos com as fibras de NaNbO3 apresentaram respostas piezoelétrica e fotoluminescente melhores do que às apresentadas pelos compósitos obtidos à partir do NaNbO3 na forma de cubos. A inclusão...
Keywords: Anisotropia; Piezoeletricidade; Fotoluminescencia; Compositos polimericos; Ferroeletricidade; Polymeric composites